'What do we have to lose?': Local economic decline, prospect theory, and support for Brexit. (December 2019) - Carreras, Miguel
Abstract: The Brexit referendum confronted British voters with a choice that could have profound consequences for the British economy in a context of high uncertainty. Drawing on important lessons from prospect theory, I argue that citizens who were in the domain of economic losses were more likely to take a risk and vote in favor of Brexit. On the contrary, I hold that citizens who were in the domain of economic gains tended to be more risk averse and were more likely to support 'Remain' in the referendum. Using data from several waves of the British Election Study 2014–2019 Internet Panel, I find strong support for these theoretical expectations. British voters who lived in declining areas were significantly more likely to think that leaving the EU would lead to improvements in the national economy. These prospective economic evaluations (captured about a month prior to the referendum) in turn are related to the 'Leave' vote in the Brexit referendum.